Systematic target actionability reviews of preclinical proof-of-concept papers to match targeted drugs to paediatric cancers - Schubert, Nil A. (Eur J Cancer, 2020)
BACKGROUND: Children with cancer are in urgent need of new therapies, as approximately 25% of patients experience a relapse and 20% succumb to their disease. Moreover, the majority of survivors suffer from clinically relevant health problems. Repurposing of targeted agents developed for adult indications could provide novel therapeutic options for paediatric cancer patients. To prioritise targeted drugs for paediatric clinical development, we applied a systematic review methodology to develop a Target Actionability Review (TAR) strategy. These TARs assess the strength and completeness of published preclinical proof-of-concept (PoC) data by structured critical appraisal of and summarising the available scientific literature for a specific target (pathway) and the associated drugs in paediatric tumours. METHODS: A sensitive literature search in PubMed was performed and relevant papers were identified. For each paper, the individual experimental findings were extracted, marked for paediatric tumour type and categorised into nine separate PoC data modules. Each experimental finding was scored for experimental outcome and quality independently by two reviewers; discrepancies were assessed by a third reviewer and resolved by adjudication. Scores corresponding to one PoC module were merged for each tumour type and visualised in a heat map matrix in the publicly available R2 data portal [r2.amc.nl]. RESULTS AND CONCLUSIONS: To test our TAR methodology, we conducted a pilot study on MDM2 and TP53. The heat map generated from analysis of 161 publications provides a rationale to support drug development in specific paediatric solid and brain tumour types. Furthermore, our review highlights tumour types where preclinical data are incomplete or lacking and for which additional preclinical testing is advisable.